2015
DOI: 10.1007/s00198-015-3045-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in volumetric bone mineral density, microarchitecture, and bone strength of distal radius and tibia in Chinese women: a high-resolution pQCT reference database study

Abstract: Age-related differences in vBMD and microarchitecture in Chinese women differed by bone compartments. Significant cortical bone loss occurred after midlife. Prominent increase in Ct.Po began at the fifth decade but appeared to be arrested before the sixth decade. Loss of trabecular bone was already evident in young adulthood and continued throughout life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 43 publications
5
44
0
3
Order By: Relevance
“…As expected, the group of postmenopausal women diagnosed with osteoporosis had a significantly higher mean age than the osteopenic or unaltered group, corroborating with results presented by other studies, since the advance in age is inversely associated with BMD (26)(27)(28) . Regarding the anthropometric variables that characterize the sample, it was observed that women with no alteration in BMD presented significantly greater height than osteoporotic women, however, with no differences for body weight or BMI.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the group of postmenopausal women diagnosed with osteoporosis had a significantly higher mean age than the osteopenic or unaltered group, corroborating with results presented by other studies, since the advance in age is inversely associated with BMD (26)(27)(28) . Regarding the anthropometric variables that characterize the sample, it was observed that women with no alteration in BMD presented significantly greater height than osteoporotic women, however, with no differences for body weight or BMI.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, most studies compare the differences between women and men without providing gender-related reference curves. (12)(13)(14)(15)(16)(17) In addition, in contrast to a recently study analyzing a Chinese female population, (23) our curves were determined considering the effects of weight and height because these parameters have important effects on structure and bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby suggesting that the bone loss density and the microarchitecture deterioration may be similar in individuals from different ethnicities. (23) This study established a set of reference data for volumetric and structural bone parameters obtained by HR-pQCT and biochemical properties by finite element analysis, according age, weight and height based on a miscegenated normal population. These results may be useful in clinical practice for interpreting fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations